A Study on the Effectiveness of Green Taxation in Promoting Eco-Friendly Businesses - Loso Judijanto (Institute of Educational, Research, and Community Service)
This study examines the effectiveness of green taxation policies in promoting and sustaining eco-friendly business practices across various economic contexts. Using a qualitative descriptive methodology with a library research approach, this research analyzes the implementation, outcomes, and challenges of green tax systems in both developed and developing economies over the past decade. The findings suggest that well-designed green taxation frameworks significantly influence business behavior toward sustainable practices, particularly when integrated with complementary policy instruments such as subsidies, regulatory frameworks, and public awareness campaigns. However, effectiveness varies considerably depending on economic structures, political will, administrative capacity, and cultural contexts. The study identifies several critical success factors including policy design consistency, stakeholder engagement, revenue recycling mechanisms, and transparent implementation frameworks. This research contributes to the growing body of knowledge on environmental fiscal reform and provides policymakers with insights for developing more effective green taxation strategies to accelerate the transition toward sustainable business ecosystems.